Metformin Synergistically Enhanced the Antitumor Activity of Celecoxib in Human Non-Small Cell Lung Cancer Cells - Cao, Nini; Lu, Yanyan; Liu, Jia; Cai, Fangfang; Xu, Huangru; Chen, Jia; Zhang, Xiangyu; Hua, Zi-Chun; Zhuang, Hongqin (Frontiers in Pharmacology, 2020)
Celecoxib has potential as an effective antineoplastic agent, but it may exhibit side effects. Given the glucose-addicted properties of tumor cells, metformin is recognized for its inhibitory effect on oxidative phosphorylation. In the present study, we aimed to combine low dose of celecoxib with metformin to alleviate the side effects of nonsteroidal anti-inflammatory drugs (NSAIDs) and overcome potential drug resistance. We found that celecoxib combined with metformin obviously suppressed cell migration and proliferation and induced cell apoptosis. Most importantly, in vivo experiments revealed the superior antitumor efficacy of combination treatment with a low dosage of celecoxib (25 mg/kg/day) without apparent toxicity. Further study of the underlying mechanism revealed that the two drugs in combination caused ROS aggregation in NSCLC cells, leading to DNA double-strand breaks and increased expression of the tumor suppressor factor p53. Elevated p53 subsequently caused cell cycle arrest and cell proliferation inhibition. The presence of metformin also sensitized NSCLC cells to celecoxib-induced apoptosis by activating caspase-9, -8, -3, and -7, upregulating the pro-apoptotic proteins Bad and Bax, and downregulating the antiapoptotic proteins Bcl-xl and Bcl-2. Moreover, the superior anticancer effect of combined therapy was also due to suppression of Raf-MEK-ERK cascades and PI3K-AKT signaling, which is conducive to overcoming drug resistance. In addition, either celecoxib alone or in combination with metformin suppressed NSCLC cell migration and invasion by inhibiting FAK, N-cadherin and matrix metalloproteinase-9 activities. Together, our study provided a rational combination strategy with a low dosage of celecoxib and metformin for preclinical cancer application.